Looking back to look ahead: a vision for soil denitrification research. Issue 1 (20th December 2019) - Almaraz, Maya; Wong, Michelle Y.; Yang, Wendy H.
Abstract: Denitrification plays a critical role in regulating ecosystem nutrient availability and anthropogenic reactive nitrogen (N) production. Its importance has inspired an increasing number of studies, yet it remains the most poorly constrained term in terrestrial ecosystem N budgets. We censused the peer‐reviewed soil denitrification literature (1975–2015) to identify opportunities for future studies to advance our understanding despite the inherent challenges in studying the process. We found that only one‐third of studies reported estimates of both nitrous oxide (N2 O) and dinitrogen (N2 ) production fluxes, often the dominant end products of denitrification, while the majority of studies reported only net N2 O fluxes or denitrification potential. Of the 236 studies that measured complete denitrification to N2, 49% used the acetylene inhibition method, 84% were conducted in the laboratory, 81% were performed on surface soils (0–20 cm depth), 75% were located in North America and Europe, and 78% performed treatment manipulations, mostly of N, carbon, or water. To improve understanding of soil denitrification, we recommend broadening access to technologies for new methodologies to measure soil N2 production rates, conducting more studies in the tropics and on subsoils, performing standardized experiments on unmanipulated soils, and using more precise terminology to refer to measured process rates (e.g., net N2 O flux or denitrification potential). To overcome the greater challenges in studying soil denitrification, we envision coordinated research efforts based on standard reporting of metadata for all soil denitrification studies, standard protocols for studies contributing to a Global Denitrification Research Network, and a global consortium of denitrification researchers to facilitate sharing ideas, resources, and to provide mentorship for researchers new to the field.